Analisis Pendapatan dan Pola Pengeluaran Rumah Tangga Petani di Desa Sidoraharjo, Kecamatan Kedamean, Kabupaten Gresik - Wahyuni, Febriani Tri; Rizkiyah, Noor; Setiawan, Risqi Firdaus (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Red onion farming households in Sidoraharjo Village, Kedamean District, Gresik Regency carry out red onion farming 3x or 3 harvest seasons in one year. Apart from farming, shallot farming households in Sidoraharjo Village, Kedamean District, Gresik Regency also carry out non-farm activities.  The income earned is used for household needs in the form of food and non-food. The income and expenditure made determine the level of welfare of shallot farming households in Sidoraharjo Village, Kedamean District, Gresik Regency. The aim of this research is to analyze the income, expenditure patterns and level of welfare of shallot farming households in Sidoraharjo Village, Kedamean District, Gresik Regency. The number of samples in this study was 35 onion farming households. The data analysis method uses quantitative descriptive methods. The results of this research show that the household income of shallot farmers comes from both agricultural and non-agricultural sources, with an average total income of IDR 190,660,086/year which comes from onion on-farm income of IDR 85,540,086, non-shallot on-farm income amounting to IDR 3,908,571, and non-farm amounting to IDR 101,828,571. This income is used for food and non-food expenses, the average expenditure for food is IDR 25,847,829 and non-food IDR 96,648,543. The welfare level of shallot farming households in Sidoraharjo Village, Kedamean District, Gresik Regency is based on the income approach, the PPSP value is 47%, so it is said that they are not yet prosperous if they only rely on income from the agricultural sector. Based on the expenditure approach, a PEP value of 21% is said to be prosperous.